2007
DOI: 10.1126/science.1149726
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Transplantation via Antibody-Based Clearance of Hematopoietic Stem Cell Niches

Abstract: Upon intravenous transplantation, hematopoietic stem cells (HSCs) can home to specialized niches, yet most HSCs fail to engraft unless recipients are subjected to toxic preconditioning. We provide evidence that, aside from immune barriers, donor HSC engraftment is restricted by occupancy of appropriate niches by host HSCs. Administration of ACK2, an antibody that blocks c-kit function, led to the transient removal of >98% of endogenous HSCs in immunodeficient mice. Subsequent transplantation of these mice w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
327
2
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 378 publications
(340 citation statements)
references
References 31 publications
6
327
2
1
Order By: Relevance
“…19 In summary, using a potentially clinic-translatable approach, we show that targeted macrophage overexpression of LXRa not only decreased atherosclerotic lesion formation, but also reduced plasma triglycerides, a major obstacle to date in LXR-based therapy of atherosclerosis. Owing to the continuous advances in HSC (and induced pluripotent stem-HSC) transplantation and gene delivery, 29,30 HSC-based lentiviral LXR gene therapy may provide a valuable option for prevention and treatment for coronary heart disease and stroke, the major clinical manifestations of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…19 In summary, using a potentially clinic-translatable approach, we show that targeted macrophage overexpression of LXRa not only decreased atherosclerotic lesion formation, but also reduced plasma triglycerides, a major obstacle to date in LXR-based therapy of atherosclerosis. Owing to the continuous advances in HSC (and induced pluripotent stem-HSC) transplantation and gene delivery, 29,30 HSC-based lentiviral LXR gene therapy may provide a valuable option for prevention and treatment for coronary heart disease and stroke, the major clinical manifestations of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of either pathway results in apoptosis. Using this information, Irving Weissman's group at Stanford University has demonstrated that blocking antibodies to c-Kit can be used to eliminate HSCs from mice and will precondition the mice for HSCT (94). This approach, using a monoclonal or small molecule, could be combined with depleting antibodies directed against T cells and natural killer cells as well as B cells, many of which exist and some of which, like anti-CD52/alemtuzumab, are in widespread clinical use (95,96).…”
Section: Reviewmentioning
confidence: 99%
“…The BiTE therapeutics "engage" the T cell using a BiAb that links CD3 + T cells to a specific antigen. 6,7 The first BiTE to be approved for clinical use in the United States is blinatumomab (Blincyto, Amgen). CAR T cells are genetically modified ex vivo to express a "chimeric antigen receptor" and are very promising cancer therapies that are still in development.…”
Section: See Page 1913mentioning
confidence: 99%
“…5 Based on this information, agents have been evaluated that (i) directly attack the host stem cell, (ii) alter adhesion of the host stem cell in the niche, or (iii) enhance donor stem cell adhesion in the niche. The first exciting discovery, reported by Czechowicz et al, 6 was that the anti-murine c-Kit monoclonal antibody (ACK2) brought about significant engraftment of congenic donor cells in severely immunodeficient mice. Unfortunately, this approach was not effective in immune-competent mice, although synergy was observed between ACK2 and nonmyeloablative TBI.…”
mentioning
confidence: 99%